Setting the desert on fire - Barr, James. (London)
xx, 362, [2] s., [16] s. resim
Keywords: "It is 1916. The Allies are struggling in the Great War. The Ottoman Sultan calls for a pan-Islamic jihad against all non-Muslims except Germans. But Sharif Husein, ruler of the holy city of Mecca, is smarting under Turkish rule, fomenting Arab nationalism and lobbying the British to support him. It seems to the British a good idea secretly to encourage an Arab revolt. Setting the Desert on Fire is a masterly account of this key moment made legendary by T. E. Lawrence, but here filled with a wide range of characters including the British Prime Minister Lloyd George, whose desire to capture 'Jerusalem by Christmas' had consequences that reverberate to this day." --